Nanoindentation and Corrosion Behavior of Additively Manufactured Ti-6Al-4V Alloy for Biomaterial Applications - DEMİRCİ, SELİM (My University, 2023)
In this study, the effect of different laser beam power on the nanoindentation and corrosion properties of Ti-6Al-4V alloys fabricated direct metal laser sintering (DMLS) method was investigated. Ti-6Al-4V samples were fabricated by DMLS method with three 34.72 J/mm3, 64.81 J/mm3 and 83.33 J/mm3 energy densities named as sample 1, sample 2 and sample 3, respectively. The microstructure and crystalline phase of Ti-6Al-4V samples were analyzed by optical microscope, SEM and XRD devices. Microstructural examinations showed that microstructure of Ti-6Al-4V samples consisted of the prior columnar β grains and α/α´ phases. The β phase proportion soared with rising laser beam power. Nanoindentation results illustrated that the order of reduced elastic modulus (Er) values was sample 1 > sample 2 > sample 3. The order of hardness (H) values followed sample 1 > sample 2 > sample 3. The H/ Er ratios were found to be 0.0338, 0.0333, and 0.032 for samples 1, 2, and 3, respectively. The H3/Er2 ratios were estimated to be 0.00734 GPa, 0.00633 GPa, and 0.00513 GPa for samples 1, 2, and 3, respectively. The presence of high values means better anti-wear capacity and good resistance to deformation for samples based on nanoindentaion findings. Moreover, electrochemical measurements depicted that the value of corrosion current density (icor) of the samples ordered as sample 3 > sample 2 > sample 1. The sample 1 exhibited better corrosion resistance than other samples. The findings showed that as the laser power is low, DMLS Ti-6Al-4V samples potentially have better mechanical and corrosion performance due to low β content and high α´ phases in the microstructure.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Mechanics of Materials; Mechanical Engineering; additive manufacturing; biomaterial; corrosion behavior; nanoindentation; Ti-6Al-4V